Pengaruh Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) dan Earning Per Share (EPS) Terhadap Harga Saham pada Perusahaan yang Terdaftar dalam Indeks LQ45 Bursa Efek Indonesia tahun 2012-2015 - Muhammad Reza Handyansyah; Dinalestari Purbawati (Jurnal Ilmu Administrasi Bisnis, 2016)
This study aimed to investigate how big the influence of Return On Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS) variables simultaneously and partially to the company's share price and which variables gave the dominant influence on stock prices. The sample in this study were 45 companies listed in the Indonesia Stock Exchange LQ45. The results using simple and multiple linear regression test showed that the company's financial performance measured by ROA, ROE, NPM and EPS had an influence on stock prices. Partially concluded that ROA, ROE and EPS significantly affected stock prices, while the ROA did not significantly affect stock prices. NPM had dominant influence towards stock prices on companies listed in the LQ45 index.